Teachers’ view of Language(s) in (CLIL) Science education: a case study in Portugal - Piacentini, Valentina (2019)
The development of meaningful environments at school for the learning of Science as well as of foreign languages is an educational concern. CLIL (Content and Language Integrated Learning), aimed at the students’ acquisition of both the foreign Language and specific subject Content, is an approach that may promote the learning of English in use during subject classes and could result in the improvement of conditions and practices of Science education. Research, actually, reveals that teaching methodologies aware of language – such as CLIL – and other semiotic modes implied in Science are beneficial for the learning of Science. Studying a CLIL programme (“English Plus” project, EP), in which Science is taught/learnt with/in English, is thus relevant. A case study on the EP project and its participants (English and Science teachers, students involved in different school years) in one lower secondary state school in Portugal was carried out. In the present research, qualitative data collected through teacher interviews are presented and discussed, with the goal of understanding the role of Language(s) (verbal language in the mother tongue or English and other representation modalities) in the teaching of Science for EP teachers, both in conventional and project classes. A greater teacher awareness and use of Language(s), when an additional language (English, here) is also present for Science education, results from this work. This contributes to research on CLIL Science studies and teacher reflections on adopting a language-focused approach for Science education, also when the mother tongue is spoken.